Positive deviance, ecologies of innovation and entrepreneurial networking - Ssekajja Mayanja, Samuel; Mapeera Ntayi, Joseph; Munene, John C.; Kagaari, James R.K.; Balunywa, Waswa; Orobia, Laura (World Journal of Entrepreneurship, Management and Sustainable Development, 2019)
The purpose of this paper is to examine the mediating role of ecologies of innovation in the relationship between positive deviance (PD) and entrepreneurial networking among small and medium enterprises (SMEs) in Uganda. Design/methodology/approach – A cross-sectional survey design using quantitative approach was employed in this study. Data were collected with the help of self-administrated questionnaires from 228 SMEs. Systematic sampling technique was used. Multiple regression data were analysed with the help of SPSS software. Findings – The results indicated that ecologies of innovation partially mediate the relationship between PD and entrepreneurial networking. Besides, PD and entrepreneurial networking are significantly related. Research limitations/implications – The data were cross-sectional in nature, thus limiting monitoring changes in resources accessed from social networks by entrepreneurs over time. Practical implications – Managers of SMEs and policy makers should pay more attention to the views of employees with divergent views, ecologies of innovation in creating a conducive environment for creativity and innovation among SMEs. Originality/value – The study of PD, ecologies of innovation and entrepreneurial networking using complexity theory among SMEs in Uganda is a contribution to literature.
Keywords: Positive deviance; Ecologies of innovation; Entrepreneurial networking; Complexity; SMEs